Diagnostics of the microstructural changes in sub-zero-processed Vanadis 6 P/M ledeburitic tool steel - Sobotová, Jana (Materiali in tehnologije, 2013)
Specimens made from P/M Vanadis 6 cold-work steel were austenitized, quenched and tempered for various combinations of the parameters. The selected sets of samples, also in the sub-zero range, were treated at a temperature of -196 °C after quenching. The microstructure was investigated as a function of the austenitizing temperature and the parameters of the sub-zero processing using transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM) and X-ray diffraction. It was found that the as-quenched microstructure is composed of martensite, retained austenite and carbides. The sub-zero processing reduced the amount of retained austenite and led to an increase in the tetragonality of the martensitic lattice. As a result, the hardness of the material was higher by 2 HRc before the tempering of the samples after the sub-zero processing, but the hardness of the sub-zero-processed material after tempering is about 2.5 HRc lower than that of the non-sub-zero-processed steel. Based on the facts that the sub-zero-processed steel contained less retained austenite and an unknown amount of the expected nano-precipitates, we expected it to have a lower capability to manifest the secondary-hardening effect.
Keywords: jeklo; toplotna obdelava; kriogena obdelava; izločki